2015
DOI: 10.1038/srep08316
|View full text |Cite
|
Sign up to set email alerts
|

Fukutin is prerequisite to ameliorate muscular dystrophic phenotype by myofiber-selective LARGE expression

Abstract: α-Dystroglycanopathy (α-DGP) is a group of muscular dystrophy characterized by abnormal glycosylation of α-dystroglycan (α-DG), including Fukuyama congenital muscular dystrophy (FCMD), muscle-eye-brain disease, Walker-Warburg syndrome, and congenital muscular dystrophy type 1D (MDC1D), etc. LARGE, the causative gene for MDC1D, encodes a glycosyltransferase to form [-3Xyl-α1,3GlcAβ1-] polymer in the terminal end of the post-phosphoryl moiety, which is essential for α-DG function. It has been proposed that LARGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…However, it has also been shown that LARGE overexpression can aggravate the dystrophic phenotype, specifically in mouse models of MDC1A, FCMD, and Fkrp related CMD (Saito et al, ; Whitmore et al, ). Resolution of this discrepancy (which may relate to a requirement for Fukutin expression (Ohtsuka et al, )) is key to considering whether (or for which subtypes) such a therapy could be advanced to patients with dystroglycanopathies.…”
Section: Congenital Muscular Dystrophiesmentioning
confidence: 99%
“…However, it has also been shown that LARGE overexpression can aggravate the dystrophic phenotype, specifically in mouse models of MDC1A, FCMD, and Fkrp related CMD (Saito et al, ; Whitmore et al, ). Resolution of this discrepancy (which may relate to a requirement for Fukutin expression (Ohtsuka et al, )) is key to considering whether (or for which subtypes) such a therapy could be advanced to patients with dystroglycanopathies.…”
Section: Congenital Muscular Dystrophiesmentioning
confidence: 99%
“…Finally, patients with Fukuyama-type congenital muscular dystrophy, a frequent disorder in Japan that presents as brain micropolygria due to improper neuronal migration, contained mutations in a novel gene called fukutin ( FKTN ) (Kobayashi et al, 1998). Although its exact function remains unknown, FKTN was postulated to be a glycosyltransferase and was found to be required for LARGE activity (Ohtsuka et al, 2015). Thus, an examination of these and other α-dystroglycanopathies converged on genes involved in the synthesis of the α-dystroglycan O -mannosyl glycan, linking the biosynthetic pathway of a complex glycan to a suite of developmental disorders.…”
Section: Genetic Approachesmentioning
confidence: 99%
“…Furthermore, forced expression of Large in fukutin-deficient embryonic stem cells also failed to recover α-DG glycosylation, however coexpression with fukutin strongly enhanced α-DG glycosylation. Together, these data demonstrated that fukutin is required for LARGE-dependent rescue of α-DG glycosylation, with important implications for LARGE-utilizing therapy targeted to myofibers [16,17]. …”
Section: Animal Models Of Dystroglycanopathiesmentioning
confidence: 99%